The ABCs of Political Economy A Modern Approach - Hahnel, Robin (Pluto Press, 2014)
This revised edition of ABCs is a lively and accessible introduction to modern political economy. Informed by the work of Marx, Veblen, Kalecki, Robinson, Minsky and other great political economists, Robin Hahnel provides the essential tools needed to understand economic issues today. Dispelling myths about financial liberalisation, fiscal austerity, globalisation and free markets, ABCs offers a critical perspective on our present system and outlines clear alternatives for the future. This second edition applies the analytical tools developed to help readers understand the origins of the financial crisis of 2007, the ensuing 'Great Recession', and why government policies in Europe and North America over the past six years have failed to improve matters for the majority of their citizens. The second edition also helps explain what is causing climate change and what will be required if it is to be resolved effectively and fairly.